Recent ecophysiological, biochemical and evolutional insights into plant carnivory - Adamec, Lubomír; Matušíková, Ildikó; Pavlovič, Andrej (Annals of botany, 2021)
BACKGROUND: Carnivorous plants are an ecological group of approx. 810 vascular species which capture and digest animal prey, absorb prey-derived nutrients and utilize them to enhance their growth and development. Extant carnivorous plants have evolved in at least ten independent lineages, and their adaptive traits represent an example of structural and functional convergence. Plant carnivory is a result of complex adaptations to mostly nutrient-poor, wet and sunny habitats when the benefits of carnivory exceed the costs. With a boost in interest and extensive research in recent years, many aspects of these adaptations have been clarified (at least partly), but many remain unknown. SCOPE: We provide some of the most recent insights into substantial ecophysiological, biochemical and evolutional particulars of plant carnivory from the functional viewpoint. We focus on those processes and traits in carnivorous plants associated with their ecological characterization, mineral nutrition, cost-benefit relationships, functioning of digestive enzymes and regulation of the hunting cycle in traps. We elucidate mechanisms by which uptake of prey-derived nutrients leads to stimulation of photosynthesis and root nutrient uptake. CONCLUSIONS: Utilization of prey-derived mineral (mainly N and P) and organic nutrients is highly beneficial for plants and increases the photosynthetic rate in leaves as a prerequisite for faster plant growth. Whole-genome and tandem gene duplications brought gene material for diversification into carnivorous functions and enabled recruitment of defence-related genes. Possible mechanisms for the evolution of digestive enzymes are summarized, and a comprehensive picture on the biochemistry and regulation of prey decomposition and prey-derived nutrient uptake is provided.
Keywords: listy rostlin; Plants; digestive enzymes; Carnivorous plant; mineral nutrient economy; fotosyntéza; terrestrial and aquatic species; masožravci; Photosynthesis; Drosera; evolution of carnivory; hunting cycle; živiny; Nepenthes; cost–benefit relationships; Carnivory; rostliny; regulation of enzyme secretion; Animals; co-option; Dionaea; zvířata; Plant Leaves; Nutrients